1999
DOI: 10.1002/1531-8257(199901)14:1<28::aid-mds1007>3.3.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and occupational factors influencing the risk of Parkinson's disease: A case‐control study in southeastern Sweden

Abstract: PURPOSE AND METHODS: To investigate the possible impact of nutritional and environmental risk factors for idiopathic Parkinson's disease (IP), a case-control study was performed in the county of O ¨stergo ¨tland in southeastern Sweden. The study involved 113 cases of IP and 263 control subjects. Dietary, drinking, and smoking habits, as well as previous occupation, were requested in a structured questionnaire.RESULTS: No increased risk was found for any of the nutritional items in which information was request… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
112
1
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(123 citation statements)
references
References 26 publications
(48 reference statements)
8
112
1
2
Order By: Relevance
“…Dopaminergic neurons are thought to have high basal levels of oxidative stress due to the highly reactive nature of dopamine (9)(10)(11). Exposure to environmental agents that induce further oxidative stress leads to selective dopaminergic neuron degeneration in animal models (6,(12)(13)(14)(15)(16), reflective of increased risk by such agents for Parkinson's disease in humans (5,12,(17)(18)(19)(20)(21)(22).…”
mentioning
confidence: 99%
“…Dopaminergic neurons are thought to have high basal levels of oxidative stress due to the highly reactive nature of dopamine (9)(10)(11). Exposure to environmental agents that induce further oxidative stress leads to selective dopaminergic neuron degeneration in animal models (6,(12)(13)(14)(15)(16), reflective of increased risk by such agents for Parkinson's disease in humans (5,12,(17)(18)(19)(20)(21)(22).…”
mentioning
confidence: 99%
“…We also accounted for the confounding effect of socioeco- O observed number of cases; SIR standardized incidence ratio; CI confidence interval nomic status. Socioeconomic status is a risk factor associated with PD [9]. Additionally, the data in the Swedish Hospital Discharge Register are highly complete.…”
Section: Discussionmentioning
confidence: 99%
“…Social isolation and low levels of emotional support are related to specific mood disorders and PD [24]. Furthermore, unhealthy behavior in psychiatric patients, such as smoking, an unhealthy diet, and physical inactivity, possible mechanisms for PD, and low socioeconomic status are related to both psychiatric disorders and PD [9,18,27]. In addition, biological mechanisms are likely involved in the development of both psychiatric disorders and PD.…”
Section: Discussionmentioning
confidence: 99%
“…There have been a wide range of reports on PD and dietary factors, such as those focusing on excessive intake of animal lipids [8][9][10][11], insufficient intake of nicotinic acid (niacin) [12][13][14], and insufficient intake of antioxidants [20].A study in Seattle by Anderson et al [11] with 4 groups of subjects consuming different amounts of animal lipids indicated that the risk of PD increased as animal lipid intake increased, with an odds ratio of 3.30 for those in the group consuming the largest amount.The authors of the report proposed that this could be due to the large effect of oxidative stress caused by animal lipid intake.In a cross-sectional study in Rotterdam focusing on the relationship between antioxidant intake and PD [15], the results indicated that is was harder for subjects in a group taking 10 mg of vitamin E per day to develop PD (OR 0.5, 95 % confidence interval; 0.2-0.9). Due to problems with the studies, however, the relationship between PD and dietary factors has as yet not been confirmed.…”
Section: ■ Parkinson's Disease and Dietary Factorsmentioning
confidence: 99%